EXPLORING BIOCLIMATISM IN THE POST-OCCUPANCY EVALUATION OF HOUSEHOLDS - Ferreira de Araújo, Leonard; Bella Sarmento Salgueiro Eliziário Matias, Emanoella (Journal of Interdisciplinary Debates, 2023)
Introduction: Housing complexes represent a significant part of the built environment in urban areas, playing a crucial role in providing housing for increasingly dense populations. However, the effectiveness of these projects in providing healthy and sustainable living environments is often questioned after occupation. Thus, this research proposes to explore the relevance of bioclimatism in the post-occupation evaluation of housing complexes. By examining this intersection between bioclimatism and post-occupation, we can identify gaps in the design, construction and management of housing complexes, thus contributing to the evolution of architectural and urban practices. Objective: To understand how bioclimatic principles influence the performance of residential buildings after occupation. Methodology: This study relies on a literature search approach to explore the role of bioclimatism in the post-occupancy assessment of housing developments. Results and Discussion: The results obtained from the post-occupancy analysis of housing complexes with a focus on bioclimatism revealed significant insights into the influence of these approaches on the performance of buildings and the well-being of occupants. The selected case studies spanned a variety of climate contexts and architectural designs, allowing for a comprehensive understanding of the impacts of bioclimatism in practice. A striking finding is that bioclimatic principles play a decisive role in the thermal comfort of living spaces. Buildings that incorporated design strategies aimed at solar orientation, cross ventilation and the use of shading elements demonstrated superior performance in maintaining adequate indoor temperatures. Conclusion: The bioclimatic approach not only improves the performance of buildings, but also creates healthier, more sustainable and more pleasant living environments. However, to maximize the benefits of bioclimatism, an ongoing effort in awareness, education and collaboration between professionals and occupants is required. The development of specific guidelines for different climate contexts and the promotion of sustainable building standards can further enhance the positive impact of bioclimatism on urban housing.